2017
DOI: 10.1038/s41598-017-10221-4
|View full text |Cite
|
Sign up to set email alerts
|

WS2 and MoS2 biosensing platforms using peptides as probe biomolecules

Abstract: Biosensors based on the two-dimensional layered nanomaterials transition metal dichalcogenides such as WS2 and MoS2 have shown broad applications, while they largely rely on the utilization of single stranded DNA as probe biomolecules. Herein we have constructed novel WS2- and MoS2- based biosensing platforms using peptides as probe biomolecules. We have revealed for the first time that the WS2 and MoS2 nanosheets display a distinct adsorption for Arg amino acid and particularly, Arg-rich peptdies. We have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…The sensing interface ability of present genosensor was compared with earlier reported MoS 2 based biosensors 3752 . High sensitivity, specificity and repeatability of the sensor make it best among other biosensors (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The sensing interface ability of present genosensor was compared with earlier reported MoS 2 based biosensors 3752 . High sensitivity, specificity and repeatability of the sensor make it best among other biosensors (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of methods reported for biomolecule immobilization onto MoS 2 involve physisorption , which suffers from problems with stability and leaching of immobilized species during sensor storage and use. Only a few studies report covalent immobilization of biomolecules atop MoS 2 . These include reports of Ni 2+ adsorption followed by protein binding through a polyhistidine tag , direct binding of carboxylate groups to MoS 2 followed by amide bond formation to proteins , and bond formation between a thiol group on the biomolecule and MoS 2 , as reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies report covalent immobilization of biomolecules atop MoS 2 . These include reports of Ni 2+ adsorption followed by protein binding through a polyhistidine tag , direct binding of carboxylate groups to MoS 2 followed by amide bond formation to proteins , and bond formation between a thiol group on the biomolecule and MoS 2 , as reported here. All studies of covalent bond formation between MoS 2 and biomolecules involve nanosheets of MoS 2 that are subsequently attached to another substrate material .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from MoS 2 , WS 2 could also act as an efficient quencher for fluorescence donors [85,[111][112][113][114][115][116][117][118][119][120]. Xi et al [111] reported for the first time that the WS 2 nanosheets were utilized to develop a FRET sensor for the detection of microRNA.…”
Section: Ws 2 Nanosheets As the Acceptor In Fret Sensorsmentioning
confidence: 99%